Dożynki 1949. (Starograd (Gdański) : [s.n.], 1949)
Afisz z inf. o dożynkach oraz programem święta.
Keywords: Święta rolnicze -- Polska -- Gdańsk (region) -- 1945-1970 -- plakaty; Starogard Gdański (Polska ; region) -- 1945-1970 -- druki ulotne; Starogard Gdański (Polska ; region) -- 1945-1970 -- plakaty; Starogard Gdański (Polska ; region) -- 1945-1970 -- źródła